The Distance Between the Cranial Nerve IX-X Root Entry/Exit Zone and the Pontomedullary Sulcus: MR Imaging Study in Patients With Hemifacial Spasm - Fang, Jixia; Lv, Gaoquan; Wang, Dongliang; Liu, Ruen (Frontiers in Neurology, 2022)
Subject: To quantitatively describe the distance between the cranial nerve (CN) IX-X root entry/exit zone (REZ) and the pontomedullary sulcus in patients with hemifacial spasm (HFS). Methods: A total of 215 outpatients with HFS were recruited. Finally, 108 patients who yielded high-quality images were enrolled in the study. MRIs were reconstructed to measure the distance between the bilateral CN IX-X REZs and the corresponding pontomedullary sulcus. Results: Among the 108 patients, the ratio of males to females was 39/69, and the mean age was 57.9 ± 6.5 years. The ratio of left to right HFS involvement was 47/61. The average height was 1.62 ± 0.07 m, and the average body mass index (BMI) was 24.65 ± 2.97 kg/m2. The distance between the cephalic end of the CN IX-X REZ and the pontomedullary sulcus was 2.7 ± 0.9 mm. The distance between the caudal end of the CN IX-X REZ and the pontomedullary sulcus was 7.6 ± 1.1 mm. No monotonic relationship was found between distance and height or BMI in the scatter diagrams. Conclusions: The CN IX-X REZ is closely related to the pontomedullary sulcus in patients with HFS, and there is no difference between the left and right sides. The distances were not correlated with height or BMI in patients with HFS.